Assessment of hepatic fat content in using quantitative ultrasound measurement of hepatic/renal ratio and hepatic echo-intensity attenuation rate. - Yun-Sheng Wang; Gui-Ping Zhang; Xiao Yang; Jun Ye; Yong-Hong Cao; Rong Zhang; Shuai Ye; Shi-Mei Xing; Er-Lan Shi; Ji Zhang; Hu Lian; Jin-Xiang Xia; et al. (Medical Ultrasonography, 2020)
Aims: This study aims to evaluate and validate a simple quantitative ultrasound (US) method for determining the hepatic fat content (HFC) based on the combination of quantitative US hepatic/renal ratio (US-HRR) and quantitative US hepatic echo-intensity attenuation rate (US-HAR) as compared with [1H]-magnetic resonance spectroscopy (1H-MRS).Material and Methods: There were a total of 242 subjects recruited in the present study. All subjects were examined for HFC by quantitative US and 1H-MRS methods. The QUS-HRR and QUS-HAR were calculated from ordinary ultrasound images of liver and kidney with a triple modality 3D abdominal phantom using the Image J software.Results: The results found that US-HRR and US-HAR correlated with 1H-MRS HFC (US-HRR: r=0.946, p<0.001; US-HAR: r=0.936, p<0.001). The equation for HFC prediction by using quantitative US was: HFC (%) = 28.965 × US-HRR + 218.045 × US-HAR - 8.892. Subgroup analysis in study subjects with body mass index (BMI) ≥28 showed that quantitative US HFC was associated with 1H-MRS HFC (R2=0.953, p<0.001). Receiver operating characteristic (ROC) analysis observed that the cut-off value of fatty liver diagnosis was 6.71% in using the quantitative US model; the sensitivity and specificity for fatty liver diagnosis were 94.15% and 96.30%, respectively. Variability analysis indicated that there was a relative high degree of consistency in the measurement of HFC with different operators or ultrasonic apparatus.Conclusions: Quantitative US measurement could be regarded as a simple, sensitive tool to accurately assess HFC. It provides a valid alternative to 1H-MRS as an easy, non-invasive option for the precise estimation of HFC in clinical practice.